Modeling of Electron and Lattice Temperature Distribution Through Lifetime of Plasma Plume (Journal of Engineering, 2014)
When employing shorter (sub picosecond) laser pulses, in ablation kinetics the features appear which can no longer be described in the context of the conventional thermal model. Meanwhile, the ablation of materials with the aid of ultra-short (sub picosecond) laser pulses is applied for micromechanical processing. Physical mechanisms and theoretical models of laser ablation are discussed. Typical associated phenomena are qualitatively regarded and methods for studying them quantitatively are considered. Calculated results relevant to ablation kinetics for a number of substances are presented and compared with experimental data. Ultra-short laser ablation with two-temperature model was quantitatively investigated. A two-temperature model for the description of transition phenomena in a non-equilibrium electron gas and a lattice under picosecond laser irradiation is proposed. Some characteristics are hard to measure directly at all. That is why the analysis of physical mechanisms involved in the ablation process by ultra-short laser pulses has to be performed on the basis of a theoretical consideration of `indirect' experimental data. For Copper and Nickel metal targets, the two-temperature model calculations explain that the temperature of the electron subsystem increased suddenly and approached a peak value at the end of laser pulse. In addition, the temperature profile of lattice temperature subsystem evolution slowly, and still increasing after the end of laser pulse. A good agreement prevails when a comparison between the present results and published results.